IFAP: helping farmers to organize themselves - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Despite the widespread rhetoric on the importance of agriculture, farmers (especially small farmers) in many developing countries are getting a raw deal. Some problems we hear all too often are: producers being excluded from project planning,...